1988
DOI: 10.1111/j.1528-1157.1988.tb03746.x
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of Antiepileptic Drugs: Analysis of Possible Risk Factors

Abstract: To determine the primary factors responsible for the increased incidence of malformation in the off-spring of antiepileptic drug (AED)-treated epileptic mothers, special attention was paid to drug combinations in a prospective study of 172 deliveries. Variables used for analysis were eight antiepileptic drugs (AEDs) and total daily dosages (drug score), and seven background factors consisting of maternal age at delivery, gravida, outcome of previous pregnancy, etiology and type of epilepsy, occurrence of seizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
2
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(67 citation statements)
references
References 19 publications
1
63
2
1
Order By: Relevance
“…The developing central nervous system (CNS) in the neonatal period has been found to be more vulnerable to the neurotoxic effects of phenytoin because of the higher brain concentration of phenytoin (Kaneko et al, 1988). Prenatal exposure to phenytoin may result in a spectrum of structural, developmental and behavioural changes known as fetal hydantoin syndrome (Nanda et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The developing central nervous system (CNS) in the neonatal period has been found to be more vulnerable to the neurotoxic effects of phenytoin because of the higher brain concentration of phenytoin (Kaneko et al, 1988). Prenatal exposure to phenytoin may result in a spectrum of structural, developmental and behavioural changes known as fetal hydantoin syndrome (Nanda et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Teratogenic effects resulting from AED treatment occur in 5-6% of infants born to women with epilepsy, which is almost double the rate of the general population (46). Certain AED combinations are associated with enhanced risk (e.g., VPA), and an enzyme-inducing AED (e.g., PB, PHT, and CBZ) enhances the risk of malformations and hepatotoxicity and therefore alternative AEDs should perhaps be considered (47)(48)(49). Furthermore, there is evidence to suggest, from a study of a relatively small number of patients receiving polytherapy, that the incidence of malformations increases with increasing number of AEDs; exposure to two, three, or four AEDs is associated with an incidence rate of malformations of 5.5, 11, and 23%, respectively (50).…”
Section: Pregnancymentioning
confidence: 99%
“…[1][2][3] The risks have been reported as 3.1% to 9.0% for major congenital malformations (MCMs), 37% for one minor abnormality (MA), and 11% for 2 MAs in offspring with in utero exposure to AEDs. 2,4 Several studies found that AED polytherapy poses a higher risk of malformation (8.6%) than that of AED monotherapy (4.5%). [4][5][6] The risk of MCMs increases to 4% to 9% after in utero exposure to the first-generation AEDs.…”
mentioning
confidence: 99%
“…2,4 Several studies found that AED polytherapy poses a higher risk of malformation (8.6%) than that of AED monotherapy (4.5%). [4][5][6] The risk of MCMs increases to 4% to 9% after in utero exposure to the first-generation AEDs. 5,7 The percentage of MCMs was reported as 6.5% for phenobarbital, 8 3.7% for phenytoin, 9 and 2.2% for carbamazepine.…”
mentioning
confidence: 99%